2002
DOI: 10.1046/j.1365-2141.2002.03247.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of cytokine‐induced killer cells from leukaemic samples with in vitro cytotoxicity against autologous 
and allogeneic leukaemic blasts

Abstract: + CIK cells generated following culture ranged between 7á6% and 65% (median of 35á3%) and these cells were able to kill the human natural killer target K562 cells. Although the same effector cells were able to lyse autologous acute myeloid leukaemia (AML) target cells, they were not able to lyse autologous acute lymphoblastic leukaemia target cells. Pre-absorption of the CIK effector cells by K562 cells did not completely abrogate the cytotoxicity of CIK cells against autologous blasts in 9 out of 12 samples t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 23 publications
1
102
0
1
Order By: Relevance
“…13 Allogeneic AML blasts from an unrelated patient's sample frozen in multiple vials at diagnosis was used as the target.…”
Section: Laboratory Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Allogeneic AML blasts from an unrelated patient's sample frozen in multiple vials at diagnosis was used as the target.…”
Section: Laboratory Assaysmentioning
confidence: 99%
“…Earlier work established the superiority of CIK cells over lymphokine-activated killer (LAK) cells in terms of expansion and cytotoxicity. 10,11 Potent in vitro cytotoxicity against various chemo-resistant tumour cell lines, 12 lymphoma, 10,11 and primary AML 13 and CML cells 14 had been reported. CIK cells 15,16 and other ex vivo expanded polyclonal T cells 17 have been used as an activated form of DLI in the post-allo-HSCT setting.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tumor cells are more susceptible to NK cells due to their lack of MHC class I. 31 33 This suggests that a combined application of NK and CIK cells may exhibit a synergistic antitumor immune response due to their selective cytotoxic activity against diverse tumor cells. 34,35 Thus, it is worthwhile to investigate the efficacy of the combined application of CIK and NK cells to treat NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…3 Cytokineinduced killer (CIK) cells are T lymphocytes enriched in CD3 + CD56 + cells, 4 which can be easily and rapidly expanded in vitro from human peripheral blood, bone marrow or cord blood mononuclear cells 5,6 with the sequential addition of interferon (IFN)-g, OKT-3 and high doses of interleukin (IL)-2. 7,8 It has been demonstrated that CIK cells can lyse a broad array of tumor targets in a non-MHC-restricted manner, 4 have the capacity to migrate toward tumor sites 9,10 and display anti-tumor activity in vivo. 7,9 In contrast, they show negligible alloreactivity and a minimal tendency to induce graft-versus-host disease as compared to allogeneic splenocytes.…”
Section: Introductionmentioning
confidence: 99%